Traditional bullying and cyberbullying: Bystander strategies - V. L. Nazarov; N. V. Averbuch (Russian State Vocational Pedagogical University, 2023)
Introduction. An important aspect of any bullying is the position of the bystander. Timely intervention by a bystander can prevent bullying or mitigate its consequences for the victim. On the other hand, the bystander may join the bullying on the aggressor's side or maintain a neutral position, which will cause the aggressor to feel impunity and increase the victimisation of the bullying object. This study compares the actions of bystanders of traditional school bullying, school cyberbullying and nonschool cyberbullying.Aim. The current study aims to define the strategy of school bullying and cyberbullying bystanders and clarify the most frequently observed forms of bullying by bystanders.Methodology and research methods. To study the problem, a questionnaire was developed designed to study the forms of bullying and witness behaviour strategies. The questionnaire survey was conducted among 1,762 middle-level students of educational organisations of general secondary education and secondary vocational training in Ekaterinburg and the Sverdlovsk Region.Results. Among the bystanders of traditional bullying, 39% prefer non-interference, 36% prefer to support the victim, 23% report bullying to parents and teachers, 0.7% join the aggressor and 1% gave the answer "other".Among the bystanders of school cyberbullying, 44.5% prefer non-interference, 24.5% support the victim, 28% inform parents, teachers or the administration of an Internet resource, 0.5% join the harassment and 1.5% gave the answer "other".Among the bystanders of non-school cyberbullying, 42.5% prefer non-interference, 25.5% support the victim, 29.5% inform parents, teachers or the administration of an Internet resource, 1% join the harassment and 1% gave the answer "other".As can be seen, the percentage of those who prefer non-interference is highest among the bystanders of school cyberbullying, while the percentage of bystanders who support the victim is highest among the bystanders of traditional bullying. The percentage of those joining the bullying on the side of the persecutor is highest among the bystanders of non-school cyberbullying.Scientific novelty. In this study, for the first time, the categories of bystanders of school and nonschool cyberbullying are divided as categories of bystanders of various processes. Among the possible strategies of behaviour of a bystander in a situation of bullying, for the first time, it is proposed to seek help from adults or from the administration of the Internet resource on the basis of which the bullying takes place.Practical significance. Based on the study of the behaviour of the bystander of bullying (traditional bullying and cyberbullying), the results of this work could be applied to develop recommendations for encouraging the bystander to intervene in bullying on the victim's side, to stop it independently or to inform teachers.